EXPLORASI NILAI TRADISI NUGAL PADI DI DESA OLAK DAN DESA ARO, PROVINSI JAMBI DARI SISI NILAI SPIRITUAL, EKONOMI, SOSIAL DAN BUDAYA - Sruni Lestari; Alya Yulieta; Nicky Handayani; Yeni Susanti; Rina Astuti; Nafa Rahmadani; Naila Ramadhani; Novita Rahmawati; Rizkya Ramadhini; Kurnia Irsanti; Darsyifa Azahra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Nugal Padi tradition in Olak and Aro Villages, Jambi Province, is an agricultural tradition steeped in spiritual, economic, social, and cultural values. This cooperative rice planting activity is not merely a chore, but a manifestation of the harmonious relationship between humans, nature, and ancestors. Spiritually, rituals such as prayer and land purification serve as expressions of gratitude to God and the forces of nature. Economically, collective work strengthens efficiency and food security, and fosters solidarity through the sharing of harvests. Its social values include strengthening community ties, norms of sharing, and preserving a sense of togetherness passed down through generations. Local culture remains alive through rituals, traditional symbols, and customs that serve as community identity and educational tools for the younger generation about hard work and gratitude. This study used a qualitative approach with observation and in-depth interviews to explore these values. The results indicate that the Nugal Padi tradition remains relevant in fostering work ethic, maintaining social and environmental balance, and strengthening cultural identity. Preserving this tradition is crucial for the sustainability of local culture and the agricultural well-being of local communities.